The Influence of Knowledge Aspects of The Multicultural on The Implementation of Multicultural Education in Elementary Schools - Suzana Muhamad Pilus; Ngoc Minh Nguyen (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This study examines the knowledge level of Multicultural Education among national school teachers in Negeri Sembilan. This study was conducted on 927 teachers who teach in national-type schools in Negeri Sembilan. This study aims to identify the influence of knowledge about multicultural education from content integration knowledge, knowledge construction, equity pedagogy, prejudice reduction and knowledge of school cultural empowerment and social structure on implementing multicultural education in primary schools. It is quantitative survey research. The questionnaire was distributed to 927 respondents consisting of teachers who teach in national-type schools in Negeri Sembilan. The data of this study was analyzed using the Statistical Package for the Social Sciences (SPSS) software version 26.0. Two types of statistics are used, namely descriptive statistics and inferential statistics. Descriptive statistics using frequency, percentage, mean and standard deviation are used to describe the profile of the respondents and answer the research questions. The data of this study was analyzed using the Statistical Package for the Social Sciences (SPSS) software version 26.0. Multiple Regression Statistics are used to identify the influence of multicultural education knowledge from knowledge of content integration, knowledge construction, equity pedagogy, prejudice reduction and knowledge of school cultural empowerment and social structure on implementing multicultural education in primary schools.